228k views
4 votes
Solve: 2cos^2(w)-cos(w)-1=0

2 Answers

7 votes

Answer:

Explanation:

2 cos²(w)-cos w-1=0

2 cos² w-2cos w+cos w-1=0

2 cos w(cos w-1)+(cos w-1)=0

(cos w-1)(2 cos w+1)=0

either cos w=1=cos 0=cos (0+2nπ)

w=2nπ,n∈I

or 2 cos w+1=0

cos w=-1/2=-cos (π/3)=cos ((2n+1)π±π/3)

w=[(2n+1)±1/3]π,

n∈ I

User RoboYak
by
4.8k points
6 votes

Answer:

w = π/2

Explanation:

I used trig identities (double angle) to solve this problem.

Step 1: Rearrange problem

2cos²(w) - cos(w) - 1 = 0

2cos²(w) - 1 - cos(w) = 0

Step 2: Trig Identity

cos2w - cos(w) = 0

Step 3: Combine like terms

cosw = 0

Step 4: Solve

w = cos^-1(0)

w = π/2

I may have done it wrong so don't rely too much on me

User Ire
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.